Tissue-specific expression of silkmoth chorion genes in vivo using Bombyx mori nuclear polyhedrosis virus as a transducing vector. - Iatrou, K (1990)
A pair of silkmoth chorion chromosomal genes, HcA.12-HcB.12, was inserted into a baculovirus transfer vector, pBmp2, derived from the nuclear polyhedrosis virus of Bombyx mori. This vector, which permits the insertion of foreign genetic material in the vicinity of a mutationally inactivated polyhedrin gene, was used to acquire the corresponding recombinant virus. Injection of mutant silkmoth pupae that lack all Hc chorion genes with the recombinant virus resulted in the infection of all internal organs including follicular tissue. Analysis of RNA from infected tissues has demonstrated that the two chorion genes present in the viral genome are correctly transcribed under the control of their own promoter in follicular cells, the tissue in which chorion genes are normally expressed. The chorion primary transcripts are also correctly processed in the infected follicular cells and yield mature mRNAs indistinguishable from authentic chorion mRNAs present in wild-type follicles. These results demonstrate that recombinant nuclear polyhedrosis viruses can be used as transducing vectors for introducing genetic material of host origin into the cells of the organism and that the transduced genes are transiently expressed in a tissue-specific manner under the control of their resident regulatory sequences. Thus we show the in vivo expression of cloned genes under cellular promoter control in an insect other than Drosophila melanogaster. The approach should be applicable to all insect systems that are subject to nuclear polyhedrosis virus infection.